2016
DOI: 10.3892/mmr.2016.5291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platelet-derived growth factor on chondrocyte proliferation, migration and apoptosis via regulation of GIT1 expression

Abstract: The formation of fibrocartilage, cartilaginous and bony calluses is vital for bone healing following a fracture. Fibroblasts, chondrocytes and osteoblasts are critical functional cells that are involved in these three processes, respectively. Platelet‑derived growth factor (PDGF), a growth factor that is released from platelet particles and appears during the early stages at the site of fractures, is essential in bone healing via regulation of cell proliferation and differentiation. However, the effects of PDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…A recent study [11] demonstrated that miR-206 overexpression significantly inhibited the proliferation, promoted chondrocyte apoptosis, dramatically decreased Col2a1 and aggrecan, and increased Runx2 and MMP-13 [11], indicating the involvement of miR-206 in cartilage degradation in OA. Furthermore, GIT1 has been shown to promote chondrocytes proliferation and inhibit chondrocytes apoptosis [12][13][14]. In the current study, we verified not only the direct binding between KLF3-AS1 and miR-206, but also 3ʹUTR of GIT1 and miR-206.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A recent study [11] demonstrated that miR-206 overexpression significantly inhibited the proliferation, promoted chondrocyte apoptosis, dramatically decreased Col2a1 and aggrecan, and increased Runx2 and MMP-13 [11], indicating the involvement of miR-206 in cartilage degradation in OA. Furthermore, GIT1 has been shown to promote chondrocytes proliferation and inhibit chondrocytes apoptosis [12][13][14]. In the current study, we verified not only the direct binding between KLF3-AS1 and miR-206, but also 3ʹUTR of GIT1 and miR-206.…”
Section: Discussionsupporting
confidence: 71%
“…Extensive research has shown that G-proteincoupled receptor kinase interacting protein-1 (GIT1) promotes chondrocytes proliferation and inhibits chondrocytes apoptosis [12]. Zhao et al [13] stated that platelet-derived growth factor (PDGF) promotes chondrocyte proliferation but suppresses chondrocyte apoptosis via upregulating GIT1 expression. A recent study also showed that [14] miR-195 inhibits the proliferation and migration of chondrocytes by targeting GIT1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that GIT1 reduces vascular smooth muscle cell apoptosis by interacting with PLCg via the SHD that contains the CC1 domain and modulation of PLCg activation (32,33). In addition, the antiapoptotic role of GIT1 is demonstrated in the fate of chondrocytes (66,67). Recently, a proteomic analysis identified GIT1 as a novel mammalian target of rapamycin complex component that is critical for mediating astrocyte survival (68).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al confirmed dependence of Methyl-CpG binding protein 2 (MeCP2)-induced the activation of ERK1/2 signals and cell proliferation on GIT1 in gastric cancer cells [11]. Furthermore, a recent study by another Dr. Zhao proved that chemical stimuli (platelet-derived growth factor, PDGF)-enhanced chondrocyte activity and functions was dependent on activated GIT1 [12]. However, it is similarly unclear whether GIT1 is stimulated, and the specific functions of GIT1 involved in modulating mechanical stress-initiated mitogenic effects,including the nature of any functional association between GIT1 and ERK1/2 in this context, remain to be elucidated in chondrocytes.…”
Section: Introductionmentioning
confidence: 74%
“…And GIT1 can be stimulated by integrin signal-associated proteins and interact with the latter, and anchor potential downstream signaling molecules, activating intracellular signaling cascades [12,19,20]. Interaction between FAK and GIT1 within signal transduction has been analyzed in several non-chondrocytic cell types, however, the conclusions are controversial [21][22][23].…”
Section: Introductionmentioning
confidence: 99%